Psychosocial illness among the drug abusers undergoing detoxification in Dhaka, Bangladesh - Zaman, Bushra; Ahmed, SM Moslehuddin; Hossain, Mir Mahmud; Kamal, Md Mustafa (South East Asia Journal of Public Health, 2015)
Abuse of drugs is a worldwide problem. Drug addiction is increasing tremendously in the South Asian countries especially in Bangladesh where such addiction is widespread among the younger age groups. It causes rapid erosion of educational, cultural, moral and family values. On the basis of defined criteria a total of 300 drug abusers who undergoing detoxification at the outpatient department of Central Drug Addiction Treatment Centre, Tejgaon, Dhaka were selected. The study was done for a period of one year from July 2013 to June 2014. Data were collected by face to face interview using pre-tested questionnaire. The analysis was done by computer using SPSS version 22.0. About 68% of the drug abusers had taken drugs for 2-5 years and 38% had taken three drugs during their life time. The major influencing factor for taking drugs was for peer pressure. Among the drug abusers 77% had taken Ganja, 60% Heroin as their first drug and 37% Yaba as their last drug. The depression was measured by the Beck's Depression Inventory that showed 55% of the drug abusers had moderate depression, 23% borderline clinical depression, 15% mild mood disturbance, 4% severe depression, and 3% had extreme depression. There were s ignificant associations between the duration of taking drugs (p<0.001), the number of taking drugs (p<0.006), and the age of first use of drugs (p<0.019) with depression. Majority of the drug abusers had depression and a significant number of them were involved in antisocial activities as well as violence. Family and social participation, behavioral therapies and proper medical management are essential to control drug addiction. South East Asia Journal of Public Health Vol.4(2) 2014: 36-41